2022
DOI: 10.3390/v14020324
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Retroviral Gag-Genomic RNA Cellular Interactions Leading to Genome Encapsidation and Viral Assembly: An Overview

Abstract: Retroviruses must selectively recognize their unspliced RNA genome (gRNA) among abundant cellular and spliced viral RNAs to assemble into newly formed viral particles. Retroviral gRNA packaging is governed by Gag precursors that also orchestrate all the aspects of viral assembly. Retroviral life cycles, and especially the HIV-1 one, have been previously extensively analyzed by several methods, most of them based on molecular biology and biochemistry approaches. Despite these efforts, the spatio-temporal mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 178 publications
0
3
0
Order By: Relevance
“…That study showed Cer1 gRNA is highly abundant in gonad cytoplasm, but did not determine whether any of the cytoplasmic gRNA was associated with GAG particles [ 24 ]. Because retroviral capsids package only two molecules of single stranded gRNA [ 54 ], we re-examined gRNA localization using smFISH (single molecule fluorescence in situ hybridization) in combination with immunostaining for GAG. Mitotic nuclei typically showed 1–2 foci of gRNA, but staining in pachytene nuclei could usually be resolved into four, closely spaced foci which presumably represent each of the four LGIII chromatids ( Fig 2C , panels 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…That study showed Cer1 gRNA is highly abundant in gonad cytoplasm, but did not determine whether any of the cytoplasmic gRNA was associated with GAG particles [ 24 ]. Because retroviral capsids package only two molecules of single stranded gRNA [ 54 ], we re-examined gRNA localization using smFISH (single molecule fluorescence in situ hybridization) in combination with immunostaining for GAG. Mitotic nuclei typically showed 1–2 foci of gRNA, but staining in pachytene nuclei could usually be resolved into four, closely spaced foci which presumably represent each of the four LGIII chromatids ( Fig 2C , panels 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Genome packaging in HIV-1 is dependent on interactions between an un-cleaved precursor PR55 NC domain and a 110 nucleotide Psi (ψ; RNA packaging signal) segment [ 94 ] in the 5′ RNA leader sequence [ 83 ]. The ψ segment comprises four stem loops (SL1–SL4) that are connected by short linkers [ 95 ]. The stem loops are proposed to have independent but redundant functions [ 94 ] which include the facilitation of genomic RNA dimerization by the dimer initiation site (DIS) in SL1; the packaging of un-spliced mRNAs when the signal is overlapped with the ψ-site by the major splice donor (SD) in SL2; heterologous RNA packaging by SL3; and the adoption of alternate structures by SL4 [ 22 ].…”
Section: Nucleocapsidmentioning
confidence: 99%
“…HIV-1 p6 comprises two unique late domains [ 102 ]. As part of the precursor PR55 Gag polyprotein, these domains recruit and bind the endosomal sorting complex required for transport (ESCRT) cellular factor to promote the abscission of immature virions from the host cell [ 95 ]. The first late domain, YPXL (Tyr-Pro-X-Leu), binds cellular factor ALG2-interacting protein X (ALIX) [ 105 ].…”
Section: P6mentioning
confidence: 99%